MORPHOLOGICAL CHARACTERISTICS OF MAGNETITE AND QUARTZ IN THE PRODUCTIVE STRATA OF NORTHERN DISTRICT OF KRYVYI RIH BASIN - Тіkhlivets S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Currently, the main task for the geological service of Hannivka deposit of the Northern Ore Mining and Processing Works is to ensure the Ore Mining and Processing Works with raw materials, which allows receiving high-quality iron ore concentrate that meets the requirements of the world market. It is only possible to meet this challenge taking into account the morphological features of the main rock-forming minerals, and as a consequence, the natural capabilities of the ores, their dressability by increasing the efficiency of the blending ores of various mineral varieties and of different technological potential, in order to achieve the optimal composition of the ore mixture, which is fed to the beneficiation plant. Morphological studies of the main minerals in unchanged and metasomatically altered ferruginous quartzites were performed according to the standard method. Measurement of the magnetite and quartz grain sizes was carried out using an eyepiece micrometer mounted on a mineralographic microscope. The determining of their average indexes was carried out with the use of mathematical methods. The results of the study of the main morphological characteristics of iron ore-bearing minerals and their variations, depending on the location within the unchanged and metasomatically altered ferruginous quartz of Hannivka deposits at Northern region are represented. The results of the study of the dihedral angles of magnetite and quartz crystals, changes in the particle size distribution of these minerals, depending on the imposed geological processes on the banded-iron formation of Kryvyi Rig basin are shown. The scientific novelty consists in detailed conducting of mineralogical researches of the magnetite and quartz morphological features depending on their location in the section of the banded-iron formation of the Kryvyi Rih basin and in the further utilization of these results in topominerological mapping of the Northern region. The obtained variability of the main minerals’ morphology of the ore-bearing strata must be taken into account in the mineral mapping of the deposit and the Northern region of the Kryvyi Rih basin in general, when specifying the mineral-technological classification of ores and the blended mineral varieties of ores before feeding to the beneficiation plant.